Children in Migration and International Family Law: The Child’s Best Interests Principle at the Interface of Migration Law and Family Law: Book Review - Nugroho Adi Wicaksono; Muhammad Ali Fauzi; Rizqi Fatkhur Rohman (Presscience, 2026)
Children in Migration and International Family Law: The Child’s Best Interests Principle at the Interface of Migration Law and Family Law, edited by Arnold and Heiderhoff (2025), is an interdisciplinary legal volume that examines how the principle of the child’s best interests operates at the intersection of international family law and migration law within the European context. Produced as part of the EU-funded FAMIMOVE project, the book addresses the often-overlooked legal and institutional gaps that arise when children and families move across borders, particularly in situations involving asylum, refugee protection, and cross-border family relations.